Drenagem e traces tectonicos na Regiao Norte-Ocidental de Estado de Sao Paulo. - Arid, F. M.; Barcha, S. F.; Pieruceti, J. A. (My University, 1983)
A detailed statistical study of the drainage was made as an indirect means for interpreting the modern tectonic traits of the area. Over 1000 measurements of direction of fluvial courses were made from maps and air photos. These data allowed the diagnosis of the existence of a regional tectonic pattern, printed on the basaltic rocks, and its influence on the drainage adjustment as well as a more local control exerted by structures present in the Bauru Group rocks. -from English summary
Drainage and tectonic traits of the northwestern region of the State of Sao Paulo
Keywords: control of drainage; Parana Basin; Photointerpretation; structural control.